Trading Modernity. Female gallerists at work for the art of their time in the first half of the 20th Century - Burcu Dogramaci (Journal of Art Historiography, 2023)
In the 1910s and 1920s, female art dealers such as Maria Kunde (Kunstsalon Maria Kunde, Hamburg) championed the art of their time. This commitment of women to contemporary art can also be followed up in exile – for example in London: Ala Story who came from Vienna was not only active in several progressive London galleries for contemporary art, but also emigrated to the USA in 1940, where she established the American British Art Center in New York. In the post-war period, art dealer Hanna Bekker vom Rath (Frankfurter Kunstkabinett) was an important advocates of the modernists banned by the Nazis, but also stood up for younger artists.